Acceptance Analysis and Nutritional Content of Kluwih Seed Milk in Fulfilling Elderly Nutrition Intake - Ratna, Ni Komang Ayu Nila (Indonesian Journal of Food Technology, 2024)
Kluwih seeds (Artocarpus communis) are a local food source that is still not widely used as a ready-to-eat food preparation. Kluwih seeds contain nutritional components such as protein, carbohydrates, fat, minerals and vitamins so that they can be used as a source of nutrients. The elderly are a group of people aged 60 years or over who currently need attention because the biological, physical and psychological aging that occurs in the elderly is feared to trigger inadequate food intake for the elderly so that adequate nutritional sources are needed. Kluwih seeds are a new inspiration to be processed into milk as a ready-to-eat food to meet the nutritional needs of the elderly. The aim of this research is to determine the acceptance of elderly people for kluwih seed milk and the percentage of nutritional content contained in kluwih seed milk. The research method used in this research is experimental. The samples in this study consisted of kluwih seed milk (P1), UHT milk (P2) and soy milk (P3). Acceptability analysis was carried out using scoring and hedonic test methods for taste, color and aroma parameters. Nutritional content analysis was carried out on the carbohydrate, protein and fat components of kluwih seed milk. Information on the acceptability of the elderly to kluwih seed milk was obtained from research subjects, namely 50 elderly panelists in 3 sample areas, namely Banjar Delod Padonan and Banjar Pengembungan, Pererenan Village and Banjar Negara, Sading Village, Mengwi District, Badung Regency, Bali. Based on the results of the hedonic test, elderly panelists in the sample area preferred kluwih seed milk (P1) over UHT milk (P2) and soy milk (P3), with the preferred characteristics of kluwih seed milk being yellowish white in color, very distinctive aroma, delicious and savory taste. The results of the nutritional content test show that kluwih seed milk contains 55.95% carbohydrates, 13.61% protein and 7.77% fat with a better nutritional ratio than UHT milk and soy milk.